Perhitungan Break Even Point (BEP) dan Margin of Safety (MOS) sebagai Alat Perencanaan Laba pada Usaha Mikro Kecil Menengah Sugi Donat - Triyana, Erfi; Kusumastuti, Endah Dwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Every businessmen has a main goal in building his business, the main goal is to make a profit. In the process of achieving this main goal, businessmen can make plans regarding the profit they want in advance. This research was conducted to plan profits in Sugi Donat's business which has a large enough number of sales but does not yet have a profit plan. The research method used is descriptive quantitative using components of the Cost-Volume-Profit analysis there are Break Even Point with a single product, Break Even Point with multiple products and Margin Of Safety. The results of the research and calculations reveal that Sugi Donut's business has a profit target of 40% and must make sales of Rp 275,483,227 with 86,089 units of sugar donut products, Rp 170,947,889 with 37,163 units of meses donut products and Rp 146,809,866 with 20,485 premium bomboloni product units so that the profit target can be achieved.